2019
DOI: 10.1159/000503382
|View full text |Cite
|
Sign up to set email alerts
|

Is Low-Dose Haloperidol Effective against Postoperative Nausea and Vomiting? A Randomized Controlled Trial

Abstract: <b><i>Background:</i></b> Nausea and vomiting are undesirable outcomes during the postoperative period. Vomiting may cause life-threatening pulmonary aspiration, as the airway reflex may not be fully restored postoperatively due to the residual effects of anesthetic and analgesic medications. <b><i>Objective:</i></b> The aim of this study is to determine the effective dosage of haloperidol against nausea and vomiting, as well as its adverse effects. <b><… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In another study that compared the effect of different doses of haloperidol against normal saline, the findings showed that haloperidol was effective compared with normal saline for PONV. 18 The Consensus guidelines for managing PONV published in 2003 did not endorse the safety and efficacy of the S-HT3 antagonist and dexamethasone to control PONV in high-risk patients, even did not endorse dexamethasone as an adjunctive therapy; while the effect of haloperidol at low doses has been confirmed. 20…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In another study that compared the effect of different doses of haloperidol against normal saline, the findings showed that haloperidol was effective compared with normal saline for PONV. 18 The Consensus guidelines for managing PONV published in 2003 did not endorse the safety and efficacy of the S-HT3 antagonist and dexamethasone to control PONV in high-risk patients, even did not endorse dexamethasone as an adjunctive therapy; while the effect of haloperidol at low doses has been confirmed. 20…”
Section: Discussionmentioning
confidence: 99%
“…Also, the study conducted by Pazoki et al 32 found that the PONV incidence was significantly higher in the normal saline group than in the other 2 groups(4 mg and 8 mg ondansetron) at 24 hours. In another study that compared the effect of different doses of haloperidol against normal saline, the findings showed that haloperidol was effective compared with normal saline for PONV 18 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations